Strategi Komunikasi Kreatif Produksi Take Me Out Indonesia Dalam Mempertahankan Rating - Fatnurrahman, Muhammad Afif; Hariyati, Farida; yuliani, Magvira; Solihin, Olih (Majalah Ilmiah UNIKOM, 2024)
Take Me Out Indonesia is a reality TV show that brings together people who are looking for life partners. The format of the show involves several stages of introduction and challenges designed to help participants showcase their personalities and interests. The objective of this study is to analyze the strategies devised by the creative team of Take Me Out Indonesia to maintain its ratings. This study employs a qualitative approach with data collection techniques through interviews. The results of this study indicate that the production process of "Take Me Out Indonesia" involves creative strategies across pre-production, production, and post-production stages. "Take Me Out Indonesia" is a program that explores numerous romance and matchmaking stories aired on the MNCTV channel. The creative strategies implemented ensure that the production process runs optimally and achieves the expected ratings, thereby sustaining the show over the desired period. Key Words: Creative strategy, production, television